Progressive Universalism? The Impact of Targeted Coverage on Healthcare Access and Expenditures in Peru - Sven Neelsen; Owen O'Donnell (Tinbergen Institute, 2016)
Like other countries seeking a progressive path to universalism, Peru has attempted to reduce inequalities in access to healthcare by granting the poor entitlement to tax-financed basic care without charge. We identify the impact of this policy by comparing the target population's change in healthcare utilization with that of poor adults already covered through employment-based insurance. There are positive effects on receipt of ambulatory care and medication that are largest among the elderly and the poorest. The probability of getting formal healthcare when sick is increased by almost two fifths, while the likelihood of being unable to afford treatment is reduced by more than a quarter. Consistent with the shallow cover offered, there is no impact on use of inpatient care. Mean out-of-pocket (OOP) expenditure on healthcare is unaffected but spending is reduced by up to one quarter at some points of the distribution. Among healthcare users, medical spending is reduced across much of the distribution and in relative terms falls most at lower quantiles, which is consistent with limited nominal and effective coverage of expensive treatments.
Keywords: H42; H51; I18; 330; Health insurance; health financing; healthcare; Universal Coverage; Peru